2012
DOI: 10.3109/00365513.2012.699098
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid haemorrhage induces an inflammatory response followed by a delayed persisting increase in asymmetric dimethylarginine

Abstract: This is an accepted version of a paper published in Scandinavian Journal of Clinical and Laboratory Investigation. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the published paper: Rodling Wahlström, M., Olivecrona, M., Koskinen, L., Naredi, S., Hultin, M. (2012) "Subarachnoid haemorrhage induces an inflammatory response followed by a delayed persisting increase in asymmetric dimethylarginine" Scandinavian Journal of Clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…19 ADMA levels were within the 0.2 to 0.4μmol/L range, which is similar to our findings, though we did not see such a marked increase. 19 Peripheral endothelial dysfunction and reduced plasma L-arginine:ADMA ratio have been shown to occur in the first 5 days after ischemic stroke, which is different from our observation: that whereas changes in ADMA and arginine do occur after SAH, the arginine:ADMA ratio remains overall stable.…”
Section: Time Coursesupporting
confidence: 81%
See 2 more Smart Citations
“…19 ADMA levels were within the 0.2 to 0.4μmol/L range, which is similar to our findings, though we did not see such a marked increase. 19 Peripheral endothelial dysfunction and reduced plasma L-arginine:ADMA ratio have been shown to occur in the first 5 days after ischemic stroke, which is different from our observation: that whereas changes in ADMA and arginine do occur after SAH, the arginine:ADMA ratio remains overall stable.…”
Section: Time Coursesupporting
confidence: 81%
“…[14][15][16][17][18] In a recent study, plasma ADMA was found to increase over the first week after SAH. 19 In addition, high concentrations of ADMA in cerebrospinal fluid have been found to associate with cerebral vasospasm in humans and in primates with experimentally induced SAH. 11,20,21 The aim of this prospective observational study was to investigate if circulating ADMA, arginine, arginine:ADMA ratio, and NOx are associated with survival after SAH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the ruptured aneurysms treated in this study were not treated in the acute phase of subarachnoid hemorrhage, studies suggest that acute-phase proteins can remain elevated for several months following subarachnoid hemorrhage. 24 Another hypothesis that has been suggested regarding the etiology of IPH is one of hyperperfusion following PED placement. This is thought to be due to a sudden loss of a large capacitance chamber in the form of a giant aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Asymmetric dimethyl arginine (ADMA), an endogenous inhibitor of nitric oxide synthase and a marker of endothelial dysfunction and inflammation, was also shown be increased starting from day 2 and was highest approximately 9–10 days after SAH. [ 76 114 ] Higher levels of macrophage migration inhibitory factor (MIF), soluble CD40 ligand (sCD40L), and platelet-derived growth factor (PDGF)-BB were also correlated with poor outcome. [ 23 70 ] aSAH patients may also experience cardiopulmonary complications as part of the systemic reaction.…”
Section: Introductionmentioning
confidence: 99%